Soft X‐ray and ENA Imaging of the Earth's Dayside Magnetosphere. Issue 3 (9th March 2021) - Connor, H. K.; Sibeck, D. G.; Collier, M. R.; Baliukin, I. I.; Branduardi‐Raymont, G.; Brandt, P. C.; Buzulukova, N. Y.; Collado‐Vega, Y. M.; Escoubet, C. P.; Fok, M.‐C.; Hsieh, S.‐Y.; Jung, J.; et al.
Abstract: The LEXI and SMILE missions will provide soft X‐ray images of the Earth's magnetosheath and cusps after their anticipated launch in 2023 and 2024, respectively. The IBEX mission showed the potential of an Energetic Neutral Atom (ENA) instrument to image dayside magnetosheath and cusps, albeit over the long hours required to raster an image with a single pixel imager. Thus, it is timely to discuss the two imaging techniques and relevant science topics. We simulate soft X‐ray and low‐ENA images that might be observed by a virtual spacecraft during two interesting solar wind scenarios: a southward turning of the interplanetary magnetic field and a sudden enhancement of the solar wind dynamic pressure. We employ the OpenGGCM global magnetohydrodynamics model and a simple exospheric neutral density model for these calculations. Both the magnetosheath and the cusps generate strong soft X‐rays and ENA signals that can be used to extract the locations and motions of the bow shock and magnetopause. Magnetopause erosion corresponds closely to the enhancement of dayside reconnection rate obtained from the OpenGGCM model, indicating that images can be used to understand global‐scale magnetopause reconnection. When dayside imagers are installed with high‐ENA inner‐magnetosphere and FUV/UV aurora imagers, we can trace the solar wind energy flow from the bow shock to the magnetosphere and then to the ionosphere in a self‐standing manner without relying upon other observatories. Soft X‐ray and/or ENA imagers can also unveil the dayside exosphere density structure and its response to space weather. Key Points: Soft X‐ray and Energetic Neutral Atom (ENA) imaging instruments provide an innovative way to visualize the global solar wind‐magnetosphere interaction High‐cadence, wide field‐of‐view soft X‐ray, and ENA images can capture the motion of the bow shock and magnetopause The magnetopause motion can reveal the magnetopause reconnection mode on a global scale